PERUBAHAN TRADISI PERKAWINAN ETNIS MELAYU DI DESA BANTAYAN HILIR KECAMATAN BATU HAMPAR KABUPATEN ROKAN HILIR - ", Asmidar; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research do in the Bantayan Hilir village, Batu Hampar subdistrict, Rokan Hilir Regency and to purpose understand about ethnic Malayan wedding tradition until now, to understand what the change tradition in ethnic Malayan wedding tradition and what the factor cause of in ethnic Malayan wedding. The title is â€Change Ethnic Malayan Wedding Tradition in the Bantayan Hilir village, Batu Hampar , Rokan Hilir Regencyâ€. Main problem in the research is how ethnic Malayan wedding tradition in Bantayan Hilir village until now, how the change type ethnic Malayan wedding tradition. Population in the research is husband/wife spouse from Bantayan Hilir Malayan marriage in 2009-2013. Removal sample with technic proporsionil random sampling. Total marriage population in 2009-2013 is 138 spouse, takeable 28 spouse sample represent of population. The method is descriptive quantitative with quantitative and qualitative analysis data. Technic aggregation data with observation and guided interview and data tabulation in type table. The general result say that ethnic Malayan wedding tradition implementation until now change experience with wedding tradition do concise, not like a yore, get obtain 75,0 % search self spouse, 35,7 % perform two tradition all at once, 50,0 % use modern tools, 28,6 % not use tools a yore, 92,9 % not perform ritually treaty, 96,4 % completely rent, 100,0 % final offer marriage in the house, 85,7 % use modern tools, 78,6 % doing seal Qurâ€™an ceremony, 50,0 % not use deliver accompany ceremony, 78,6 % not use tradition, 92,9 % use pencak silat, 39,3 % doing by family, 71,4 % use titi kain ceremony, 39,3 % sit in state direct only, 53,6 % not use embroidery cloth, 96,4 % doing slice cake ceremony, 96,4 % not use repeatedly ceremony. Change type happen is big change to many people and small change to a little people. The change factor cause of formal education system factor progress is 46,4 %, self search materialism perspectiveis 60,7 %, have to much money, idealism perspective is 82,1 % use music orchestra and influence factor other society culture is 89,3 % follow modern.Key word: Change, Tradition, Ethnic Malayan Wedding